#EleN\~ao: Economic crisis, the political gender gap, and the election of Bolsonaro - Laura Barros; Manuel Santos Silva (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2019)
After more than one decade of sustained economic growth, accompanied by falling poverty and inequality, Brazil has been hit by an economic recession starting in 2014. This paper investigates the consequences of this labor market shock for the victory of far-right Jair Bolsonaro in the 2018 presidential election. Using a shiftshare approach and exploring the differential effects of the recession by gender and race, we show that heterogeneity in exposure to the labor demand shock by the different groups is a key factor explaining the victory of Bolsonaro. Our results show that male-specific labor market shocks increase support for Bolsonaro, while female-specific shocks have the opposite effect. Interestingly, we do not find any effect by race. We hypothesize that, once facing economic insecurities, men feel more compelled to vote for a figure that exacerbates masculine stereotypes, as a way of compensating for the loss in economic status. Women, on the other hand, when confronted with economic shocks and the prospect of Bolsonaro's election, respond by rejecting his political agenda in favor of a more pro-social platform.
Keywords: D72; J16; J23; P16; R23; 330; economic shocks; populism; gender; voter participation